Examining the Relationship Between Brand Value, Energy Production and Economic Growth - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2022)
The aim of this study is to determine the relationship between the energy production of the USA between 2010-2019 and the brand value of an energy company (oil and gas) selected from this country and the economic growth of the country. Multiple Linear Regression Model was used to measure whether there is a significant relationship between these variables or the effect of the relationship. Data for analysis were obtained annually from the World Bank, EIA and Brand Finance. During the study phase, Variance inflation factors for the independent variables (VIF) test, Breusch-Pegan/Cook Weisberg test, Breusch-Godfrey LM test and Shapiro-Wilk W test were applied. In the study, energy production and brand value of an energy company were used as independent variables, and economic growth was used as dependent variables. As a result of the latest regression analysis, it has been determined that there is a positive linear relationship between the dependent and independent variables of the country. In the study, it was concluded that the increase in energy production in the USA and the increase in the brand value of the relevant energy company positively affected the economic growth of this country.